2016
DOI: 10.1103/physreva.94.023816
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon vibrational excitation of air by long-wave infrared laser pulses

Abstract: Ultrashort long-wave infrared (LWIR) laser pulses can resonantly excite vibrations in N 2 and O 2 through a two-photon transition. The absorptive, vibrational component of the ultrafast optical nonlinearity grows in time, starting smaller than, but quickly surpassing, the electronic, rotational, and vibrational refractive components. The growth of the vibrational component results in a novel mechanism of 3 rd harmonic generation, providing an additional two-photon excitation channel, fundamental + 3 rd harmoni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…As in our prior results at λ ≤ 2.4µm in the mid-IR [11], there is little dispersion in 𝑛𝑛 2 . In the region near λ=8.0µm for N2, which was scanned continuously through 7.5-8.5 µm, we observed no signature of 2-photon resonant absorption [10].…”
Section: � 𝑚𝑚mentioning
confidence: 56%
See 1 more Smart Citation
“…As in our prior results at λ ≤ 2.4µm in the mid-IR [11], there is little dispersion in 𝑛𝑛 2 . In the region near λ=8.0µm for N2, which was scanned continuously through 7.5-8.5 µm, we observed no signature of 2-photon resonant absorption [10].…”
Section: � 𝑚𝑚mentioning
confidence: 56%
“…In this Article we present measurements of the detailed spatiotemporal profiles of femtosecond laser pulses in the infrared wavelength range 𝜆𝜆 = 2.5 − 11𝜇𝜇𝜇𝜇, and the absolute nonlinear response of major air constituents (N2, O2, and Ar) over this range. We also investigate possible resonant 2-photon vibrational excitation of N2 near λ=8µm, which is of interest for high power LWIR laser pulse propagation [10]. The spatiotemporal measurements reveal the wavelength-dependent pulse front tilt and temporal stretching induced by the difference frequency generation scheme used to generate the infrared pulses.…”
mentioning
confidence: 99%
“…Recent theoretical work on mid-IR pulse propagation in gases has predicted that at long wavelengths, selfcompression and self-steepening give rise to single-cycle pulses and a supercontinuum that spans multiple octaves [17]. Mid-IR/LWIR ultrashort pulses have been shown to exhibit drastically different propagation dynamics than pulses in the near-IR, including optical shock formation [17][18][19][20], accelerated third-harmonic generation via vibrational excitation of N 2 and O 2 [21], extended and smooth filamentation [22,23], and a significant defocusing contribution due to many-body effects, leading to long-range self-channeling [24]. Furthermore, Panagiotopoulos et al [18] have theoretically demonstrated long-range, highpower 3-D spatio-temporal solitary waves (i.e., light bullets [25,26]) in air via mid-IR laser filamentation.…”
mentioning
confidence: 99%
“…because the tan −1 converges to a constant. The modified formula, equation (8), indicates that the qualitative behavior of THG is changed by the relationship between Δ Laser and γ. Palastro et al [2] discussed the interference between two-photon absorption and THG. We do not consider the interference effect because the target length used in our study is much shorter than that in [2] and the third harmonic is considerably weak compared with the pumping pulses.…”
Section: Theorymentioning
confidence: 99%
“…Of the many theoretical and experimental studies on general THG, She and Billman [1] investigated the theory of using the vibrational states of diatomic molecules for THG and found that a high conversion efficiency of up to 30% could be expected in hydrogen gas using an optimized column density and an input laser intensity of 34 MW cm −2 . Palastro et al [2] discussed vibrational two-photon absorption and THG by nitrogen and oxygen and their effects on the propagation of ultrafast long-wave infrared pulses. However, as far as we know, there have been no experimental studies on THG using the vibrational states of diatomic molecules, perhaps because it may be difficult to generate high-intensity mid-infrared pulses with a narrow linewidth, which are desired for the preparation of high coherence.…”
Section: Introductionmentioning
confidence: 99%